“El sistema de inyección TDI y el proceso de enseñanza-aprendizaje en los estudiantes del tercero de bachillerato “B” de la Unidad Educativa Carlos Cisneros de la ciudad de Riobamba en el año 2016”. - Cuvi Arellano, Braulio Javier (2016)
This investigation probed that the students did not understand what was taught by the teacher, for this reason the investigation of the TDI injection system and the teaching –learning process was carried out I the students of the third year of “B” baccalaureate of the Carlos Cisneros educational unit of the city of Riobamba in the year 2016;the general objective was to determine the TDI injection system and the teaching-learning process; the specifics were to investigate the operation of TDI injection system establish the methodology for the teaching learning process of the TDI injection system and apply the methodology; the hypothesis was how does the TDI system injection affect the teaching learning process of the students ?;the type of study was inductive ,documentary, field and transverse ;the level of diagnostic and exploratory study ;the population studied was 30 students ;the methods used were the survey as a technique and the questionnaire as an instrument; the main result indicates that teachers in 63%only sometimes use the teaching methodology appropriate to the characteristic of the group and the subject, that is why students do not understand the class; as the most important conclusion we have investigate the operation of the TDI injection system finding that students in 53% know little about the process of such a system, this is a serious future park will not be able to perform as good professionals and this will bring problems when go to college, because they are going to have shortcomings so that when they have to go out to work, it will be difficult for them to practice their profession.